2023
DOI: 10.1002/arch.22008
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free quantitative mass spectrometry analysis of the circadian proteome of Drosophila melanogaster lethal giant larvae mutants reveals potential therapeutic effects of melatonin

Abstract: Mutation in the Drosophila melanogaster lethal giant larvae (lgl), a tumor suppressor gene with a well‐established role in cellular polarity, is known to results in massive cellular proliferation and neoplastic outgrowths. Although the tumorigenic properties of lgl mutant have been previously studied, however, little is known about its consequences on the proteome. In this study, mass spectrometry‐based label‐free quantitative proteomics was employed to investigate the changes in the head and intestinal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Glutathione‐ S ‐transferase (GST) was shown to be suppressed by preparations of chili pepper that extended lifespan in D. melanogaster (Semaniuk et al, 2022a, 2022b). It was also shown that different isoenzymes of GST can be differentially regulated and affected by circadian rhythms (Wong et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione‐ S ‐transferase (GST) was shown to be suppressed by preparations of chili pepper that extended lifespan in D. melanogaster (Semaniuk et al, 2022a, 2022b). It was also shown that different isoenzymes of GST can be differentially regulated and affected by circadian rhythms (Wong et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that different isoenzymes of GST can be differentially regulated and affected by circadian rhythms (Wong et al, 2023).…”
Section: The Influence Of Akg On the Activities Of Glycolytic Antioxi...mentioning
confidence: 99%